Proses Manajemen Risiko Gadai Emas Baitul Maal Wat Tamwil Usaha Gabungan Terpadu Sidogiri Cabang Klampis Bangkalan Madura - Rifki Satriyo Aji; Muhammad Nafik Hadi Ryandono (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
The purpose of this research is to find out the risk management conductivity of sharia gold mortgage product in BMT of sidogiri’s integrated joint venture in Klampis Bangkalan Madura branch. The research method used in this research is descriptive narrative with case study method whereas this research is done by doing interview and direct observation. The findings of this research showed the management has carried out contract (aqd) in its sharia gold mortgage product since the beginning until the billing process which use the value of kinship for risk management with the result that the member (borrower) feels embarrased at the time when the installment payment has not been paid. The management will not put the mortgaged gold on auction when the member (borrower) still has good intention in paying on installment the principal financing of the sharia gold mortgage product.